(untitled) (Cultura Económica, 2019)
Since the eighties different authors have been studying the relation of economic processes of growth to technological transformations. At that moment the main vision was to consider technological changes as external to economic processes in themselves. This conception was modified with the discovery of close links between knowledge and technological innovation and business success. Thus, the role of technological changes was recognized as being part of the economic system, especially in relation to foreign trade. In this article, Javier Villanueva analyses these issues in relation to the changes that are taking place in economics.